Implementation of the Independent Curriculum in Islamic Religious Education: A Qualitative Study of Madrasahs in West Aceh, Indonesia - Marhamah Marhamah; Zikriati Zikriati; Sy. Rohana; Maisarah Maisarah (AL-ISHLAH: Jurnal Pendidikan, 2026)
The implementation of the Independent Curriculum represents a significant reform in Indonesia’s education system, emphasizing flexibility, student-centered learning, and character development. However, its application in Islamic Religious Education (IRE) within madrasahs remains underexplored, particularly in regional contexts such as West Aceh. This study employed a qualitative descriptive approach to investigate the implementation of the Independent Curriculum in IRE. Data were collected through semi-structured interviews with 3 madrasah principals and 12 IRE teachers, complemented by document analysis. The data were analyzed using thematic analysis involving data reduction, categorization, and interpretation. The findings indicate that the Independent Curriculum has been implemented across madrasah levels (MI, MTs, and MA) with institutional support through training, supervision, and provision of learning resources. Teachers demonstrated adequate ability in planning teaching modules, applying student-centered learning methods, and conducting formative and summative assessments. However, challenges persist, including limited teacher competence in differentiated instruction, inadequate use of information technology, and difficulties in designing varied assessment instruments. Efforts to address these challenges include participation in professional development, collaborative learning among teachers, and increased institutional support. The study highlights that while implementation is generally progressing well, its effectiveness is contingent upon teacher readiness and continuous professional development. Strengthening pedagogical competence and digital literacy is essential to optimize curriculum implementation. The Independent Curriculum in IRE has been implemented with moderate success in West Aceh madrasahs, but targeted interventions are needed to enhance teacher capacity and ensure more effective and sustainable implementation.